The Effect of Benson Relaxation Techniques with Sholawat Tibbili Qulub to Reduce Pain in Post-Caesarean Mothers at Dr. M.M. Dunda Limboto Regional Hospital - Harismayanti, Harismayanti; Retni, Ani; Handayani, Wiwin; Pikoli, Viranti Desilia (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
A Caesarean Section is a surgical procedure where an incision is made on the anterior wall of the uterus to facilitate the delivery of the baby. This study aims to evaluate the effectiveness of the Benson relaxation technique, supplemented by the practice of Sholawat Tibbil Qulub, in alleviating pain among mothers following a Caesarean section in the postpartum ward of RSUD Dr. MM Dunda Limboto in Gorontalo Regency. This research employs a quantitative design, utilizing a quasi-experimental one-group pre-test and post-test methodology. The sample comprised 15 respondents, all mothers in the post-Caesarean section period. The findings indicate that applying the Benson relaxation technique in conjunction with prayer significantly reduces pain levels, as demonstrated by the T-Test, which yielded a p-value of 0.000 (p-value < 0.05). This result suggests that a considerable number of mothers reported a reduction in their pain levels, albeit not complete relief. In conclusion, comparing pain levels prior to and after the implementation of the Benson relaxation technique reveals a notable decrease in pain among the respondents. It is recommended that mothers recovering from a Caesarean section consider utilizing Benson therapy alongside prayer to help mitigate their discomfort.